Optimizing the Empowerment of BUMDes 'Pesaguan Mandiri' in Clean Water Provision to Improve the Health and Welfare of the Pesaguan Kanan Village Community - Salawati, Salawati; Budiasi, Yanti; Erion, Erion (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to optimize the empowerment of BUMDes "Pesaguan Mandiri" in providing sustainable access to clean water to improve the health and well-being of residents in Pesaguan Kanan Village, Matan Hilir Selatan District, Ketapang Regency. Using a qualitative case study approach, data were collected through in-depth interviews, direct observations, and document analysis involving BUMDes managers, village officials, and local residents. The results indicate that the provision of clean water is hindered by several interrelated factors, including limited capital, lack of human resource capacity in financial and managerial aspects, and the scarcity of freshwater sources due to coastal seawater intrusion. Despite these challenges, BUMDes "Pesaguan Mandiri" plays a pivotal role in mobilizing village-owned resources and infrastructure to enhance clean water services. The novelty of this study lies in highlighting a community-based model for managing water resources in rural coastal areas vulnerable to seawater intrusion. The findings offer practical implications for local governments and development practitioners in formulating integrated and participatory strategies to strengthen BUMDes as a key actor in rural infrastructure development and public service delivery.